Expression markers of human skeletal muscle associated with disorders of glucose metabolism in the basal and postprandial state - P. A. Makhnovskii; N. S. Kurochkina; T. F. Vepkhvadze; A. O. Tomilova; E. M. Lednev; M. V. Shestakova; D. V. Popov (Сахарный диабет)
BACKGROUND. Skeletal muscles play a key role in the organism’s carbohydrate metabolism. Dysregulation of insulin-dependent glucose uptake in skeletal muscle disrupts carbohydrate metabolism in the organism and can lead to the development of obesity and type 2 diabetes.AIM. To identify expression markers (genes) of human skeletal muscle associated with disorders of glucose metabolism in the basal state and after a mixed meal normalized for body mass.MATERIALS AND METHODS. The study involved three groups of 8 people: healthy volunteers, obese patients without and with type 2 diabetes. Venous blood samples were taken in the morning (09:00) after an overnight fast and 30 min, 60 min, 90 min, 120 min, and 180 min after ingestion of a mixed meal normalized by body mass (6 kcal/kg). Biopsy samples from m. vastus lateralis was taken before and 1 h after a meal to assess gene expression (RNA sequencing) and search for genes correlating with markers of impaired glucose metabolism in the basal and postprandial state.RESULTS. Strong correlations (|ρ|>0.7 and p<0.001) between the gene expression and the level of insulin, C-peptide, glucose or glycated hemoglobin in the basal and/or postprandial state was found for 75 genes. Of these, 17 genes had marked differences (>1.5-fold) in expression between healthy people and patients, or differences in expression changes in response to a meal. We can note genes whose role in impaired glucose metabolism has already been shown earlier (FSTL1, SMOC1, GPCPD1), as well as a number of other genes that are promising for further study of the mechanisms of insulin resistance in skeletal muscle.CONCLUSION. Skeletal muscle expression markers were identified as promising candidates for future targeted studies aimed at studying the mechanisms of insulin resistance and searching for potential therapeutic targets.